Association between prenatal maternal infection and disordered eating behaviours in adolescence: a UK population-based prospective birth cohort study. Issue 6 (2nd April 2020) - Solmi, Francesca; De Stavola, Bianca L.; Khandaker, Golam M.; Bulik, Cynthia M.; Dalman, Christina; Lewis, Glyn
Abstract: Background: Prenatal infections have been proposed as a putative risk factor for a number of psychiatric outcomes across a continuum of severity. Evidence on eating disorders is scarce. We investigated whether exposure to prenatal maternal infections is associated with an increased risk of disordered eating and weight and shape concerns in adolescence in a large UK birth cohort. Methods: We used data from the Avon Longitudinal Study of Parents and Children. The primary exposure was maternal experience of infections at any time in pregnancy. Study outcomes were presence of any, monthly or weekly disordered eating at 14 and 16 years of age, and weight and shape concerns at 14 years. We defined the causal effect of the exposure on these outcomes using a counterfactual framework adjusting our analyses for a number of hypothesised confounders, and imputing missing confounder data using multiple imputation. Results: In total, 4884 children had complete exposure and outcome data at age 14 years, and 4124 at 16 years. Exposed children had a greater risk of reporting weekly disordered eating at both age 14 [risk difference (RD) 0.9%, 95% confidence interval (CI) −0.01 to 1.9, p = 0.08] and 16 (RD 2.3%, 95% CI 0.6–3.9, p < 0.01), though evidence of an association was weak at age 14 years. Exposed children also had greater weight and shape concerns at age 14 years (mean difference 0.15, 95% CI 0.05–0.26, p < 0.01). Conclusions: Exposure to prenatal maternal infection is associated with greater risk of disordered eating in adolescence. This association could be explained by in utero processes leading to impaired neurodevelopment or altered immunological profiles. Residual confounding cannot be excluded.